2018
DOI: 10.1016/j.jams.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Acupuncture as Auxiliary Treatment for Chronic Headache

Abstract: Acupuncture can be considered an auxiliary treatment for chronic headache, reducing the intensity of pain, the number of crisis, the quantity of analgesics used, and improving the quality of life in patients with this painful condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Quality of life was evaluated before and after treatment with the Brazilian version of the quality-of-life questionnaire: SF-6D, 2002. Participants in the true acupuncture group for TTH showed statistically significant improvement in all domains and improvement in overall quality of life [ 16 ]. Another prospective, randomized, controlled study with 401 patients with complaints of chronic headache (mostly migraine) in the primary care network in England and Wales compared acupuncture (12 sessions in three months) with medication and routine care.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Quality of life was evaluated before and after treatment with the Brazilian version of the quality-of-life questionnaire: SF-6D, 2002. Participants in the true acupuncture group for TTH showed statistically significant improvement in all domains and improvement in overall quality of life [ 16 ]. Another prospective, randomized, controlled study with 401 patients with complaints of chronic headache (mostly migraine) in the primary care network in England and Wales compared acupuncture (12 sessions in three months) with medication and routine care.…”
Section: Reviewmentioning
confidence: 99%
“…Another prospective, randomized, controlled study with 401 patients with complaints of chronic headache (mostly migraine) in the primary care network in England and Wales compared acupuncture (12 sessions in three months) with medication and routine care. The acupuncture group had a steeper improvement in symptom scale (acupuncture 34% improvement/control 16% improvement), 22 fewer days of headache, used 15% less medication and had 25% fewer visits to the doctor [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have studied the impact of acupuncture on many disorders such as musculoskeletal diseases 7 , chronic lower back pain 8 , nausea in pregnancy 9 and headache 10 . Researchers have also shown that acupuncture is effective for the treatment of many cancer symptoms caused by chemotherapy or radiotherapy, such as nausea 11 , vomiting 11 , cancer pain 12 , hot flashes 13 , and fatigue 14 .…”
Section: Introductionmentioning
confidence: 99%